Association Between GSK3β Gene Polymorphisms (rs334558 and rs3755557) with Schizophrenia Risk - Maryam Montazeri Dehbarez; Dormohammad Kordi Tamandani; Nasim Naeimi; Shahram Vaziri; Mohammad Shekari (Journal of Genetic Resources)
Numerous studies have recognized GSK3ß as a gene associated with susceptibility to schizophrenia (SZ), highlighting its essential function in neurodevelopment and its potential as a target for antipsychotic medications. In this study, we examined the connection between two polymorphisms of the GSK3ß gene, rs334558 and rs3755557, and their potential link to the risk of schizophrenia. We performed a case-control analysis to investigate this relationship within a population from southern Iran. DNA samples were isolated from 100 cases with schizophrenia and 100 normal controls. Then, we used a polymerase chain reaction (PCR) followed by the restriction fragment length polymorphism method (PCR-RFLP) to examine the GSK3ß SNPs (rs334558 and rs3755557) patterns. The frequency of genotypes, alleles, and the Hardy-Weinberg equilibrium were evaluated. Research has shown that individuals with the TA genotype and those with the combined TA+AA genotype at the rs3755557 (T/A) locus have a significantly higher risk of developing schizophrenia (OR= 2.94; 95% CI: 1.54-5.61, P= 0.0001) and (OR= 3.78; 95% CI: 2-7.13, P< 0.0001), respectively. Similarly, the GA genotype and the combination of GA+AA genotypes at the rs334558 (G/A) locus also notably increase the risk of schizophrenia, (OR= 6.62; 95% CI: 3.4-13; P< 0.001) and OR = 7.63; 95%CI: 3.95-14.7; P< 0.001), respectively. In this investigation, our findings have elucidated a substantial correlation between polymorphisms in the GSK3ß gene and the susceptibility to schizophrenia. The analysis indicated that variations in genotype frequencies between the control and the patient group could serve as a diagnostic criterion for schizophrenia. It is recommended that subsequent research involving larger sample sizes across diverse genetic populations be conducted to corroborate the current findings.